2019
DOI: 10.3390/ma12040603
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Anode Electrode Composited Cu–Sn Alloy and Separator for Microscale Lithium Ion Batteries

Abstract: A novel integrated electrode structure was designed and synthesized by direct electrodepositing of Cu–Sn alloy anode materials on the Celgard 2400 separator (Cel-CS electrode). The integrated structure of the Cel-CS electrode not only greatly simplifies the battery fabrication process and increases the energy density of the whole electrode, but also buffers the mechanical stress caused by volume expansion of Cu–Sn alloy active material; thus, effectively preventing active material falling off from the substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…As exemplified in Figure 3.A, the presence of Pb 2+ in a RSSs is evidenced in CV by the apparition of a peak pair placed at E Pb2+/Pb = -0. More interestingly, comparing Figures 1A and 3A, we observed that the high amount of Cu present in the RSSs induce a considerable attenuation of the Sn and Pb metals dissolution peaks and a significant distortion of the Cu dissolution peak, suggesting the formation of the Cu-Sn [16] and Cu-Sn-Pb [17] alloys during the electrodeposition step.…”
Section: Electrochemical Measurements In Real Sample Solutionsmentioning
confidence: 79%
“…As exemplified in Figure 3.A, the presence of Pb 2+ in a RSSs is evidenced in CV by the apparition of a peak pair placed at E Pb2+/Pb = -0. More interestingly, comparing Figures 1A and 3A, we observed that the high amount of Cu present in the RSSs induce a considerable attenuation of the Sn and Pb metals dissolution peaks and a significant distortion of the Cu dissolution peak, suggesting the formation of the Cu-Sn [16] and Cu-Sn-Pb [17] alloys during the electrodeposition step.…”
Section: Electrochemical Measurements In Real Sample Solutionsmentioning
confidence: 79%
“…Hence, supercapacitors (SC) can provide a higher power density with respect to batteries [22]. In this case, SC is used in place of lithium-ion batteries that limit instantaneous high power [23,24]. SC has a small capacity, but it has the merits to control high power output [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Investigations of Cu 6 Sn 5 include first principle calculations and phase transition analysis on the electrode 13 and an array of fabrication methodologies. [17][18][19][20][21] The application of complex 3D microstructures 19,20 and distinct particle geometries 21,22 in these alloy electrodes are common.…”
mentioning
confidence: 99%